What a beast! : a look-it-up guide to the monsters and mutants of mythology - Kelly, Sophia (New York : Scholastic, 2010)
Describes some of the creatures and monsters in Greek mythology.
Includes bibliographical references (p. 120-121) and index.
G8
Keywords: Monsters -- Encyclopedias, Juvenile; Mythology, Greek -- Encyclopedias, Juvenile; Monsters; Mythology, Greek